PULSE WIDTH MODULATION FOR HIGH PERFORMANCE HYBRID STEPPER MOTOR (Journal of Engineering, 2024)
This paper presents a high performance vector control approach of the current and speed for Hybrid Stepper Motor (HSM) to improve the dynamic performance of the motor. This is the basic advantage of stepper motors over other types of motors. The open loop controller shows a poor dynamic performance. The stepper motors are widely used in precise motions which is required a high dynamic. However, an open loop control is insufficient, so a closed loop control is required. The field oriented control will improve the dynamic performance of the stepper motor which becomes as a high- dynamic ac- servo. A design and implementation model of HSM using in MATLAB/ Simulink is given. The model is based on nonlinear equivalent circuits representing the operation of the motor. The simulation results of the HSM are compared with practical results of reference design kit (RDK) stepper motor, and a close agreement is noticed.